Preludes to the Inquisition: self-censorship in medieval astrological discourse. - Avelar de Carvalho, Helena (Annals of Science, 2020)
Astrologers have exercised self-censorship throughout the centuries in order to fend off criticism. This was largely for religious reasons, but social, political, and ethical motivations also have to be taken into account. This paper explores the main reasons that led astrologers to increase censorship in their writings in the decades that preceded the Church's regulations and offers some examples of this self-imposed restraint in astrological judgements.